Marine biological macromolecules as matrix material for biosensor fabrication - Bedi N.; Srivastava D.K.; Srivastava A.; Mahapatra S.; Dkhar D.S.; Chandra P.; Srivastava A. (My University, 2025)
The ocean covers two-third of our planet and has great biological heterogeneity. Marine organisms like algae, vertebrates, invertebrates, and microbes are known to provide many natural products with biological activities as well as potential sources of biomaterials for therapeutic, biomedical, biosensors, and climate stabilization. Over the years, the field of biosensors has gained huge attention due to their extraordinary ability to provide early disease diagnosis, rapid detection of various molecules and substances along with long-term monitoring. This review aims to focus on the properties and employment of various biomaterials (carbohydrate polymers, proteins, polyacids, etc.) of marine origins such as alginate, chitin, chitosan, fucoidan, carrageenan, chondroitin sulfate, hyaluronic acid, collagen, marine pigments, marine nanoparticles, hydroxyapatite, biosilica, lectins, and marine whole cell in the design and development of biosensors. Furthermore, this review also covers the source of such marine biomaterials and their promising evolution in the fabrication of biosensors that are potent to be employed in the biomedical, environmental science, and agricultural sciences domains. The use of such fabricated biosensors harnesses the system with excellent specificity, selectivity, biocompatibility, thermal stability, and minimal cost advantages. © 2022 Wiley Periodicals LLC.